Prevalence and associated factors of malaria in Pushparajgarh block of district Anuppur, Madhya Pradesh, India - Dwivedi, Manish Kumar; Bakshi, Sanjeev; Shyam, Birjhu Singh; Shukla, Ravindra; Singh, Prashant Kumar; Sharma, Naveen Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: The current study aimed to determine the prevalence of malaria and its association with seasonality of malaria and socio-demographic variables in a tribal dominated district Anuppur (Madhya Pradesh). Methods: This cross-sectional study was based on blood films for malaria parasites (BFMP) data obtained from primary health centers, sub-health centers, community health centers and district hospital. This study was also based on household survey for information on malaria awareness and type of treatment preferred for malaria. From 2014-2016, a household survey was conducted regarding the type of treatment available, assessment of the influence of demographic factors, knowledge, awareness and education on malaria occurrence. Odds ratio were used to analyse the association between the gender, age group, season and types of malaria infection. Results: Annual blood examination rate (11.81%) and slide vivax rate (0.66%) was highest in 2016. There was decrease in slide falciparum rate in 2016 (1.52%). Slide positivity rate was 3.78%, 3.73% and 2.74% in the years 2014-16. Annual parasite incidence rate was 3.20%, 3.82% and 3.07% in the years 2014-16. Plasmodium falciparum positivity rate was 78.13%, 78.17% and 54.49% in the study years and was highest among the females and in the age group of 26 years and above. Distinct seasonality was observed correlating with population dynamics of the vector and climatic and socio-demographic conditions. Conclusions: The prevalence of malaria in tribal dominated Pushparajgarh area showed seasonality that was governed by mosquitogenic factors, their transmission and socio-demographic status of the population.